On authority : a philosophical dialogue - Pappas, Nicholas J. (Algora Publishing, 2021)
"A philosophical treatment of the idea of authority, this book is a dialogue between three characters. "Director," a philosopher, challenges the others to think through their ideas of authority, how it is established, how it works, and how it can be either subtle or bold"--